Factors Limiting Policy Recognition of the New Innovation Approaches - Noor Rizawati Nasir , Asnul Dahar Minghat (International Journal of Advanced Science and Technology, 2020)
There is a growing body of literature in the field of new innovation approaches, which importance has also garnered the interest of policymakers around the world. Various policy initiatives have been introduced, and some of them have proven to be successful, reaching millions of people worldwide. The primary motive of implementing these initiatives is to generate more effective and sustainable solutions to cater to the increasingly complex socio-economic challenges. However, despite the significant contributions, previous studies revealed that these innovations received comparatively less attention in public policy as compared to conventional innovations, resulting in limited prioritisation in public policy agenda. Therefore, the purpose of this paper is to explore the factors behind the low policy recognition of new innovation approaches. Based on the literature review carried out, several factors limiting the policy recognition have been identified, in which, to some extent, have consequently limited the potential of such innovations to thrive. The role of the government, particularly the policymakers, is to respond to current issues and chart future directions supported by other stakeholders. Henceforth, their commitment to developing more balanced policy measures is indeed imperative to optimise the benefits of innovations to society and tailor them to the Sustainable Development Goals.